2005
DOI: 10.1111/j.1745-4573.2006.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Turkish‐style Sucuk Made With Different Combinations of Beef and Hen Meat

Abstract: Mixtures of beef and spent laying hen meat (100/0, 90/10, 80/20, 70/30, 50/50) were investigated for production of Turkish‐style sucuks as semidry fermented sausage. During the fermentation period (0–6 days), weight loss increased, shrinkage in diameter occurred and moisture content decreased. Weight loss of the control (100% beef/0% hen) sucuk was the lowest. Increasing the amount of spent hen meat in the sucuks up to 50% increased weight losses. The best sensory scores occurred with 50/50 (beef/hen meats) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Kayaardi and Gok (2004) found that moisture content of sucuk decreased from about 60 to 36%. Saricoban et al . (2006) consider that quality sucuk generally contains 40–35% water while Bozkurt and Bayram (2006) state that there may be a relation between moisture and overall sensory scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kayaardi and Gok (2004) found that moisture content of sucuk decreased from about 60 to 36%. Saricoban et al . (2006) consider that quality sucuk generally contains 40–35% water while Bozkurt and Bayram (2006) state that there may be a relation between moisture and overall sensory scores.…”
Section: Resultsmentioning
confidence: 99%
“…Sucuk is a Turkish-style sausage, very popular in Turkey and a number of Middle East countries, as well as Europe (Ercoskun and Özkal 2011). Sucuk and similar sausages are made of beef, sheep and goat meat and tail fat (Saricoban et al 2006) with salt, garlic and other ingredients such as sugar, nitrites and/or nitrates, and various spices (Soyer et al 2005); starter cultures can also be added (Bozkurt and Bayram 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Use of poultry meat in sucuk manufacture has advantages and disadvantages. It has been indicated that replacing beef with chicken meat in sucuk manufacture provides lower fat content, lower stearic (C18:0) and higher linoleic (C18:3) fatty acid contents however, even though up to 50% chicken addition to sucuk batch increases sensory score for color and odor, generally, increasing the amount of chicken meat in the sucuk results in lighter color, less red hue, more yellow hue, lower flavor intensity and overall acceptability (Saricoban, Karakaya, & Caner, 2006;Yilmaz et al, 2002).…”
Section: Processing Technologymentioning
confidence: 99%
“…Some aspects of traditional fermented sucuk were studied in literature including: physical, chemical and microbiological properties during processing (Gökalp & Ockerman, 1985;Gürakan, Bozo glu, & Weiss, 1995;Sarıçoban, Karakaya, & Caner, 2006), the effect of ingredients (Aksu & Kaya, 2004;Kayaardı & Gök, 2004), biogenic amine contents (Ayhan, 2001), the formation of biogenic amines during processing (Ayhan, Kolsarıcı, & Alsancak, 1999;Bozkurt & Erkmen, 2002;Vural, 1998), pathogenic bacterial load of commercial sucuks (Çolak, Hampikyan, Ulusoy, & Bingol, 2007;Gökalp, Yetim, Kaya, & Ockerman, 1998;Siriken, Pamuk, Özakın, Gediko glu, & Eyigör, 2006), and the survival behavior/inhibition of pathogens (Çalıcıo glu, Faith, Buege, & Luchansky, 2002;Coş ansu & Ayhan, 2000;Hwang et al, 2009;Kaban & Kaya, 2006;Kaya & Gökalp, 2004;Turantaş & Ünlütürk, 1991). However, a study about kinetic modeling of quality parameters of traditional fermented sucuk was not present.…”
Section: Introductionmentioning
confidence: 99%